Strategic flexibility and consistency at manager level: The compatibility between strategic enforcement and personality traits - Heru Santosa Hadiyanto, (Asian Academy of Management Journal, 2023)
There is an inconsistent relationship between personality traits and strategic enforcement. Strategic enforcement can be defined in two orientations, namely flexibility and consistency. This research aims to confirm the influence of personality traits on strategic enforcement in Indonesia’s financing companies. This research is important because this industry is facing stagnant growth due to changes in the business environment. Data from 242 respondents were collected using a stratified random sampling technique, and the partial least square (PLS) program was used to analyse the correlation between variables. The results showed that managers who tend toward strategic flexibility can be identified by their personality traits, such as their approach to gathering information, decision-making, and relate with the external world. However, sources of energy do not significantly influence strategic flexibility. On the other hand, strategic consistency can be identified by personality traits such as a source of energy and decision-making. However, the way of gathering information and relate with the external world did not show a significant influence on strategic consistency. Therefore, if top management requires more strategic flexibility, managers with an intuitive, judging, and thinking-oriented personality will be more aligned with this strategy. Conversely, if top management wants to implement strategic consistency, managers with introverted and feeling-oriented personality traits will be more aligned with this strategy.